The Psychophysics of Learning Implications for Learning Systems Design and Configuration. - Moye, John N. (Emerald Publishing Limited, 2021)
The Psychophysics of Learningpresents a learning system design approach that is formulated by the strategies and techniques the brain uses to process external information and make sense of that information to the learning ecology of all learners.